دراسة العالقة المتبادلة بين أثار البيئة السيئة في عمر إطراف األقواس المشيدة من الخشب البالستيكي والخسائر الزحفية - عباس رولا عبد الخضر (Al-Nahrain Journal of Science, 2012)
In this study an attempt capitalize on wood industry residues in Iraqi architecture after particle wood production in the construction of halls in engineering arches due to environment absence of good timber species. On the subject attended of particles thermosetting wood consists of unsaturated of polyester reinforced of beech wood shell particles again say wood shell particles once